2000
DOI: 10.1046/j.1364-3703.2000.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomato spotted wilt virus—positive steps towards negative success

Abstract: Taxonomy: Tomato spotted wilt virus (TSWV) is the type member of the plant-infecting Tospovirus genus in the family Bunyaviridae, a large group of predominantly vertebrate- and insect-infecting RNA viruses. Physical properties: Virions are 80-120-nm pleomorphic particles with surface projections composed of two viral glycoproteins, G1 and G2 (Fig. 1). Virion composition is 5% nucleic acid, 70% protein, 5% carbohydrate and 20% lipid. The genome consists of three negative or ambisense ssRNAs designated S (2.9 kb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 68 publications
0
66
0
15
Order By: Relevance
“…M RNA encodes the precursor of two glycoproteins (Gn and Gc) that incorporate in the outer envelope/membrane of host-origin and a non-structural protein NSm playing role in the virus movement. From the S RNA, two proteins are translated: the nucleocapsid (N) and a nonstructural protein (NSs) [14]. According to de Ronde et al [15], NSs is the suppressor protein of the host plant gene silencing mechanism and it is responsible for breakdown of the plant's resistance (avirulence factor, avr).…”
Section: Introductionmentioning
confidence: 99%
“…M RNA encodes the precursor of two glycoproteins (Gn and Gc) that incorporate in the outer envelope/membrane of host-origin and a non-structural protein NSm playing role in the virus movement. From the S RNA, two proteins are translated: the nucleocapsid (N) and a nonstructural protein (NSs) [14]. According to de Ronde et al [15], NSs is the suppressor protein of the host plant gene silencing mechanism and it is responsible for breakdown of the plant's resistance (avirulence factor, avr).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that substitution C118Y has occurred independently three times in the studied isolates by convergent evolution, whereas the substitution T120N was a unique event. Analysis of rates of non-synonymous and synonymous changes at individual codons showed that substitution C118Y was positively selected.Tomato spotted wilt virus (TSWV) is one of the most economically important plant viruses and causes damage in many agronomic crops worldwide (Adkins, 2000). TSWV is the type member of the genus Tospovirus, which contains the only plant-infecting members of the family Bunyaviridae.…”
mentioning
confidence: 99%
“…Tomato spotted wilt virus (TSWV) is one of the most economically important plant viruses and causes damage in many agronomic crops worldwide (Adkins, 2000). TSWV is the type member of the genus Tospovirus, which contains the only plant-infecting members of the family Bunyaviridae.…”
mentioning
confidence: 99%
“…The S RNA segment encodes the nucleocapsid (N) and NSs proteins, the M RNA segment encodes glycoproteins (Gn and Gc) and NSm proteins, and the L RNA segment encodes the RNA-dependent RNA polymerase (RdRp) (Adkins, 2000). The numerous N proteins encapsidate viral genome RNAs and, in association with a few RdRps, constitute vRNP (viral ribonucleoprotein) complexes (Uhrig et al, 1999;Richmond et al, 1998).…”
Section: Introductionmentioning
confidence: 99%